Development of the compact city index and its application to Japanese cities. (May 2015) - Lee, Jungchan; Kurisu, Kiyo; An, Kyoungjin; Hanaki, Keisuke
This study is an attempt to develop an internationally applicable compact city index that measures the performance of physical urban forms with regard to compact city policies. Based on key characteristics of the compact city that are high density, mixed land-use, and public transport systems, we formulate a new index called 'compact city index' (CCI) to assess urban compactness of populations, facilities and amenities centred on public transport systems at both community and city levels. Then sensitivity analyses follow simulating different scenarios varying hypothetical urban forms to check a dominant bias to specific variables in the CCI equation. Finally four types of CCI, in different measurements of time and distance, are applied to 41 middle-sized Japanese cities. It is found that cities can achieve urban compactness in the time aspect by utilisation of well-networked public transport systems, even though physical urban forms of those cities are largely sprawled.